Dynamicity and persistence of severe acute respiratory syndrome coronavirus-2 antibody response after double dose and the third dose with BBV-152 and AZD1222 vaccines: A prospective, longitudinal cohort study - Parai, Debaprasad; Choudhary, Hari Ram; Dash, Girish Chandra; Behera, Susmita; Mishra, Narayan; Pattnaik, Dipti; Raghav, Sunil Kumar; Mishra, Sanjeeb Kumar; Sahoo, Subrat Kumar; Swain, Aparajita; Mohapatra, Ira; Pattnaik, Matrujyoti; et al. (Frontiers in Microbiology, 2022)
Introduction: Vaccines are available worldwide to combat coronavirus disease-19 (COVID-19). However, the long-term kinetics of the vaccine-induced antibodies against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has not been sufficiently evaluated. This study was performed to investigate the persistence and dynamicity of BBV-152 (Covaxin)- and AZD1222 (Covishield)-induced immunoglobulin-G (IgG) antibodies over the year and neutralizing antibodies’ status after the one-month post booster dose. Methods: This 52-week longitudinal cohort study documented antibody persistence and neutralizing antibodies status among 304 health care workers (HCW) from six hospitals and research facilities in Odisha, enrolled during January 2021 and continued till March 2022. IgG antibodies against spike receptor-binding domain (RBD) of SARS-CoV-2 were quantified in an automated chemiluminescence immune assay-based (CLIA) platform and a surrogate virus neutralization test (sVNT) was performed by enzyme-linked immunosorbent assay (ELISA). Results: Among these 304 double doses vaccinated, 154 HCWs (50.66%) were Covaxin recipients and the remaining 150 (49.34%) were Covishield recipients. During the seven times follow-ups, a total of 114 participants were identified as vaccine breakthrough cases. In 190 non-infected HCWs, the median antibody titre was significantly waned from DD2 to DD10, both for Covaxin (231.8 AU/mL vs 42.7 AU/mL) and Covishield (1884.6 AU/mL vs 369.2 AU/mL). No statistically significant differences in antibody titers were observed based on age, gender, comorbidities, and blood groups. The median inhibition activity of sVNT was increased from 23.8% to 91.3% for Covaxin booster recipients and 41.2% to 96.0% for Covishield booster recipients. Among 146 booster dose recipients, 48 were breakthrough cases after booster and all were contracted by the omicron variant. Conclusion: This year-long follow-up study found a 7-fold and 5-fold antibody waning in Covaxin and Covishield recipients without any breakthrough infection history. However, individuals with booster breakthrough had mild symptoms and did not require hospital admission. The data also indicate the possible escape of omicron variants despite the presence of vaccine-induced neutralizing antibodies.